1997
DOI: 10.1507/endocrj.44.701
|View full text |Cite
|
Sign up to set email alerts
|

The Positive Charge of the Imidazole Side Chain of Histidine7 Is Crucial for GLP-1 Action.

Abstract: Abstract.Glucagon-like peptide-1(7-36)amide/(7-37)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…Unfortunately, the N-terminal selective chemical pegylation of GLP-1 peptides results in a monoconjugated derivative with negligible in vivo activity due to the fact that the N-terminal histidine residue is crucial for effective receptor recognition and maintenance of biological action [18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the N-terminal selective chemical pegylation of GLP-1 peptides results in a monoconjugated derivative with negligible in vivo activity due to the fact that the N-terminal histidine residue is crucial for effective receptor recognition and maintenance of biological action [18,19]. …”
Section: Discussionmentioning
confidence: 99%
“…Other amino acids in the N-terminus at positions 10 (glycine), 12 (phenylalanine), 13 (threonine), 15 (aspartate), and at positions 28 and 29 in the C-terminus are also directly involved in the receptor interaction. [121314] Alteration of these sites should theoretically lead to modification of GLP-1 resistant to DPP-4 inhibition, thereby prolonging its half-life and efficiency.…”
Section: Glucagon-like Peptide-1 Systemmentioning
confidence: 99%
“…Structure-activity studies in mammalian cells identified His 7 , Phe 12 , Phe 28 , and Ile 29 as being essential for function [86,87,88]. Hareter et al [87] reported that modification or substitution of His 7 resulted in an almost complete loss of biological activity and that this residue could possibly attracted to the negatively charged carboxylic group of Asp 15 as suggested in glucagon.…”
Section: Glp-1mentioning
confidence: 99%
“…Hareter et al [87] reported that modification or substitution of His 7 resulted in an almost complete loss of biological activity and that this residue could possibly attracted to the negatively charged carboxylic group of Asp 15 as suggested in glucagon. Adelhorst et al [88], additionally, demonstrated that side chains in positions 7, 10, 12, 13, and 15 are engaged in the receptor interaction, while residues at positions 28 and 29 are important for GLP-1 to adopt the architecture recognized by the receptor.…”
Section: Glp-1mentioning
confidence: 99%